Immigration and Work-Related Injuries: Evidence from Italian Administrative Data - Caterina Alacevich; Catia Nicodemo (Institute of Labor Economics (IZA), 2019)
There is growing evidence that foreign-born workers are over represented in physically demanding and dangerous jobs with relatively higher injury hazard rates. Given this pattern, do increasing inflows of foreign-born workers alleviate native workers' exposure to injuries? This paper provides evidence of the effects of immigration on the incidence and severity of workrelated accidents. We combine administrative data on work-place accidents in Italy with the Labour Force Survey from 2009 to 2017. Our approach exploits spatial and temporal variation in the distribution of foreign-born residents across provinces. Using province fixed-effects and an instrumental variable specification based on historical settlements of immigrants, we show that inflows of foreign-born residents drive reductions in the injury rate, paid sick leave, and severity of impairment for natives. Next, we investigate potential underlying mechanisms that could drive this effect, such as increased unemployment and selection of the workforce, and the sorting of native workers into less physically demanding jobs. Our results rule out that decreased injuries are driven by higher native unemployment. We find that employment rates are positively associated with immigration, in particular for workers with higher education. While not statistically significant at conventional levels, we also find that average occupational physical intensity for natives is lower in provinces that receive larger foreign-born inflows.
Keywords: C55; J61; J28; I1; 330; immigration; labour-market flexibility; work-related injuries; health